Transitioning out of elite sport: the experience of integrated support-team members - Mazur, P. M.; Lopez Lamas, J. E.; Wesner, M.; Schubert, T.; McLaughlin, B.; Mosewich, A. D. (The Sport Psychologist, 2025)
Integrated support teams (ISTs) are composed of multidisciplinary performance-support professionals dedicated to enhancing the performance of elite athletes. IST roles involve unique demands, particularly during the understudied career transitions. This study explored lived experiences of IST members transitioning out of elite sport roles, emphasizing the barriers and facilitators to successful transitions. Using an interpretive description framework, six former IST members (four physicians and two physiotherapists; four women and two men) who supported Canadian international-level teams participated in semistructured interviews conducted between October 2022 and January 2023. Themes encapsulated pretransition (preparing transition plan), during-transition (service continuity, communication variation, lack of support, and seeking mentorship), and posttransition phases (coping with emotions, managing identity, and reconciling aspirations). Barriers included poor organizational oversight, role instability, and ego involvement, and facilitators were social support, continuing meaningful work, and transition involvement. Our findings suggest that formalized processes, mentoring, and resource provision are essential for IST member support and service continuity.